Subjective theories of the Chilean teachers’ union about school climate and violence after the pandemic: a study of web news - Castro-Carrasco, Pablo; Cuadra-Martínez, David; Gubbins, Verónica; Rodríguez-Pastene-Vicencio, Fabiana; Carrasco-Aguilar, Claudia; Caamaño-Vega, Vladimir; Zelaya, Martina (Frontiers in Education, 2024)
IntroductionThe COVID-19 pandemic increased school violence and worsened the school climate in Chile. In Chile, punitive control policies such as the Safe Class Law (Ley Aula Segura) have been adopted. A key actor in the public debate is the Chilean Teachers’ Union, due to its potential impact on new public policies on the issue.ObjectivesThe aim of this study was to reconstruct the subjective theories of school violence and school climate presented by the Chilean Teachers’ Union after the COVID-19 pandemic, in its public discourse broadcast on the web news.MethodsBased on a documentary study, a case study design and qualitative methodology, embedded in the FONDECYT project No. 1231667, titled “The social construction in Chile of school climate and school violence after the return to face-to-face education,” web news (N = 36) were analyzed in which the Chilean Teachers’ Union explains school violence and school climate after the pandemic.ResultsWe found subjective theories that explain the meaning of school violence and school climate, and external factors associated with the serious deterioration of these educational dimensions after the COVID-19 pandemic. Accordingly, we obtained a set of measures such as inclusive policies, curriculum, participation in the development of educational policies, and refunding public education that teachers propose to solve these phenomena in the future.DiscussionIn the context of a union that has historically considered public policies to be non-participative in their formulation and distant from the schools’ reality, these findings have important implications for understanding the arguments of the Teachers’ Union about the need to improve mental health and working conditions as crucial elements for addressing school climate and school violence.